2021
DOI: 10.1002/emp2.12438
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits among people with cancer: Frequency, symptoms, and characteristics

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 33 publications
1
53
0
1
Order By: Relevance
“…All the other studies only report data on patients requiring more than one ER visit, with percentages ranging from 2 to 30% [11,17]. Although GPs can manage most symptoms at home, these hospital and ER admissions could be for treatment of difficult to manage symptoms, such as drainage for symptomatic ascites, intensified pain management or symptomatic treatment of bowel obstruction [18]. Such hospital visits should not necessarily be considered harmful to patients, but could be part of good collaboration between hospital specialists and the GP [19].…”
Section: Discussionmentioning
confidence: 99%
“…All the other studies only report data on patients requiring more than one ER visit, with percentages ranging from 2 to 30% [11,17]. Although GPs can manage most symptoms at home, these hospital and ER admissions could be for treatment of difficult to manage symptoms, such as drainage for symptomatic ascites, intensified pain management or symptomatic treatment of bowel obstruction [18]. Such hospital visits should not necessarily be considered harmful to patients, but could be part of good collaboration between hospital specialists and the GP [19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cancer patients are more likely to visit an ED for acute care when compared to the general population [11]. Due to the increasing frequency of patients with cancer presenting to the ED for acute complications of their primary cancer or cancer treatment regimen, emergency physicians should acknowledge their vital role in the care of patients with cancer.…”
Section: Implications For Education and Training In Emmentioning
confidence: 99%
“… 2 5 6 Left unmanaged, these symptoms can negatively impact patient quality of life 6 7 and functional ability, 8 and contribute to potentially avoidable emergency department visits and hospitalizations. 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…Across the cancer continuum, patients may experience multiple, concurrent symptoms, including pain, fatigue, nausea, vomiting, anxiety, depression and more 2 5 6. Left unmanaged, these symptoms can negatively impact patient quality of life6 7 and functional ability,8 and contribute to potentially avoidable emergency department visits and hospitalizations 9–11…”
Section: Introductionmentioning
confidence: 99%